Comparison of Interleukin-6 Plasma Concentration in Multisystem Inflammatory Syndrome in Children Associated With SARS-CoV-2 and Pediatric Sepsis - Diaz, Franco; Bustos B, Raúl; Yagnam, Felipe; Karsies, Todd J.; Vásquez-Hoyos, Pablo; Jaramillo-Bustamante, Juan-Camilo; Gonzalez-Dambrauskas, Sebastián; Drago, Michelle; Cruces, Pablo (Frontiers in Pediatrics, 2021)
Importance: Multisystem Inflammatory Syndrome in Children (MIS-C) associated with SARS-CoV-2 infection is thought to be driven by a post-viral dysregulated immune response, where interleukin-6 (IL-6) might have a central role. In this setting, IL-6 inhibitors are prescribed as immunomodulation in cases refractory to standard therapy. Objective: To compare plasma IL-6 concentration between critically ill children with MIS-C and sepsis. Design: a retrospective cohort study from previously collected data. Setting: Individual patient data were gathered from 3 different international datasets. Participants: critically ill children between 1 month-old and 18 years-old, with an IL-6 level measured within 48 hours of admission to intensive care. Septic patients were diagnosed according to Surviving Sepsis Campaign definition, and MIS-C cases were diagnosed by CDC criteria. Exposure: none Main Outcome(s) and Measure(s): The primary outcome was IL-6 plasma concentration in MIS-C and sepsis group at admission to the intensive care unit. We described demographics, inflammatory biomarkers, and clinical outcomes for both groups. A subgroup analysis for shock in each group was done. Results: We analyzed 66 patients with MIS-C and 44 patients with sepsis. MIS-C cases were older (96[48,144] vs 20[5,132] months old, p<0.01), but no differences in sex (41%vs43% female, p=0.8) compared to septic group. Mechanical ventilation use was 48.5%vs93%(p< 0.001), vasoactive drug use 79%vs66%(p=0.13), and mortality 4.6%vs34.1%(p< 0.01) in MIS-C group compared to sepsis. IL-6 was 156[36, 579]ng/dL in MIS-C and 1432[122, 6886]ng/dl in sepsis (p< 0.01), while no significant differences were observed in procalcitonin (PCT) and c-reactive protein (CRP). 52/66(78.8%) patients had shock in MIS-C group, and 29/44(65.9%) had septic shock in sepsis group. Septic shock had higher plasma IL-6 concentration than other sub-groups. Differences in IL-6, CRP, and PCT were not statistically different between MIS-C with and without shock. Conclusions and Relevance: IL-6 plasma concentration was elevated in critically ill MIS-C patients but at levels much lower than those of sepsis. Furthermore, IL-6 levels don't discriminate between MIS-C cases with and without shock. These results lead us to question the role of IL-6 in the MIS-C’s pathobiology, diagnosis, clinical outcomes, and, more importantly, the off-label use of IL-6 inhibitors for these cases.